TOTAL SELENIUM AND CELULAR VIABILITY FOR OBTAINING SELENIUM-YEAST - Rodríguez Best, Carmen Alicia (2019)
Selenium-yeast is obtained by the culture of Saccharomyces cerevisiae LALVIN Bourgovin RC 212 in the medium YEPD, with sodium selenite addition (concentrations of 2 to 10 mg Se(IV)/L) during exponential growth phase, after 48 hours at 30°C and 200 rpm. Total intracellular selenium quantification in the selenium-yeast is feasible with the starch-iodine spectrophotometric method at 590 nm and the addition of 8 mg Se(IV)/L yields the most biomass, a >90% cellular viability, pink coloration and a total intracellular selenium of 738±30 mg/kg in dry basis Finally, the used methodology to find the cellular viability and the analytical method proposed to determine the total intracellular selenium are accessible for monitoring the bioprocess.